A Search for a Cortical Map of Auditory Space - Middlebrooks, John C. (J Neurosci, 2021)
This is the story of a search for a cortical map of auditory space. The search began with a study that was reported in the first issue of The Journal of Neuroscience (Middlebrooks and Pettigrew, 1981). That paper described some unexpected features of spatial sensitivity in the auditory cortex while failing to demonstrate the expected map. In the ensuing 40 years, we have encountered the following: panoramic spatial coding by single neurons; a rich variety of response patterns that are unmasked in the absence of general anesthesia; sharpening of spatial sensitivity when an animal is engaged in a listening task; and reorganization of spatial sensitivity in the presence of competing sounds. We have not encountered a map, but not through lack of trying. On the basis of years of negative results by our group and others, and positive results that are inconsistent with static point-to-point topography, we are confident in concluding that there just ain't no map. Instead, we have come to appreciate the highly dynamic spatial properties of cortical neurons, which serve the needs of listeners in a changing sonic environment.